1992
DOI: 10.1002/bjs.1800790107
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriology of anal fistulae

Abstract: Anal fistulae are said to arise from cryptoglandular infection of the anal glands, which lie within the intersphincteric space. The type and virulence of the micro-organism responsible may determine whether an anal fistula develops. The microbiology of chronic anal fistulae has not been reported previously. Twenty-five consecutive anal fistulae were studied prospectively (eight intersphincteric fistulae, 12 trans-sphincteric fistulae, two suprasphincteric fistulae, one extrasphincteric fistula, one superficial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1
3

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 6 publications
0
30
1
3
Order By: Relevance
“…Anal fistula is the most frequent symptom of anorectal TB (80∼91% of cases) (7)(8)(9) and anal TB is commonly seen in men (4:1 ratio) and …”
Section: Resultsmentioning
confidence: 99%
“…Anal fistula is the most frequent symptom of anorectal TB (80∼91% of cases) (7)(8)(9) and anal TB is commonly seen in men (4:1 ratio) and …”
Section: Resultsmentioning
confidence: 99%
“…42 However, studies assessing microbiological changes in Crohn's fistulae are sparse. One study, in which 13 Crohn's patients with perianal disease had pus aspirated from their fistula tracts and analyzed by standard bacterial culture techniques, reported that Gram-positive organisms, in particular staphylococci, streptococci, and corynebacter, predominated over Gram-negative enteric organisms, 43 in contrast with findings in idiopathic fistula 44,45 where the microbiota found on excised granulation tissue were analyzed and found to be largely of gastrointestinal origin. These trials are limited by differences in the compartments analyzed (exudates versus mucosa) and the use of bacterial culture as opposed to molecular techniques to quantify the microbiota, which are inadequately selective and unable to detect the totality of microbiota within the GI tract.…”
Section: Microbiological Factorsmentioning
confidence: 94%
“…Seow-Choen et al 45 studied granulation tissue from the tracks of idiopathic perianal fistulae in 18 patients and processed the samples using standard microbiological techniques. Sixty-nine isolates representing at least 17 species were obtained.…”
Section: Comparison With Idiopathic Fistulaementioning
confidence: 99%
“…Die mikrobiologische Untersuchung weist i. d. R. eine Mischflora auf und ist für die Behandlung der kryptoglandulären Analfisteln nicht relevant [243,382]. Dies wurde auch in einer aktuellen Studie [437] bestätigt.…”
Section: Epidemiologieunclassified